Development of an occupational-therapy-led paediatric burn telehealth review clinic - Debra Phillips; Lauren Matheson; Tilley Pain; Gail Kingston (James Cook University, 2021)
Context: Burns are a common injury in children. Rural and remote children with burn injuries are disadvantaged if their burns require hospitalisation and specialist rehabilitation. Most specialist burn rehabilitation is provided in regional or metropolitan cities by a multidisciplinary team. Therefore, rural and remote burn patients are required to travel to access these services. This project aimed to develop an Occupational Therapy (OT)-Led Paediatric Burn Telehealth Review Clinic (OTPB Clinic) at Townsville University Hospital (TUH) to provide ongoing rehabilitation to rural and remote children after burn injury closer to home. Issues: Local audits identified inequitable service delivery to children from rural and remote areas after burn injury. A project officer was appointed to develop the OTPB Clinic, including comprehensive guidelines to support sustainability. An expanded scope role was undertaken by the treating OT, and allied health assistants were engaged to promote efficient service delivery. Lessons learned: The OTPB Clinic commenced in 2017 and was evaluated using patient satisfaction surveys and number of clinical encounters pre- and post-implementation. During the implementation period, 28 rural or remote paediatric burn patients were reviewed. Review frequency increased from 20-week to 8-week intervals. Travel time was reduced by approximately 12 hours per appointment. Families identified numerous benefits of the clinic including continuity of care and reduced time away from work. Less than 4% of patients required re-engagement with paediatric surgeons for surgical intervention. The model has the potential to be transferred to other tertiary referral burns services.